1987
DOI: 10.2172/6210815
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for the calculation of 3-D ICRF (Ion Cyclotron Range of Frequencies) fields in tokamak geometry

Abstract: A computational scheme is developed which permits tractable calculation of three-dimensional full-wave solutions to the Maxwell-Vlasov equations under • typical Ion Cyclotron Range of Frequencies (ICRF) experimental conditions; The method is unique in that power deposition to the plasma is determined via* the anti-Hermitian part of a truncated warm-plasma dielectric operator, rather than as the result of an assumed phenomenological collisioa frequency. The-.^ resulting computer code allows arbitrary variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This fact might have been anticipated by recalling that the net area under the imaginary part of the generalized phase integral, Z ( [ , x ) . is always positive (SMITHE et al, 1988).…”
Section: Cmentioning
confidence: 98%
See 1 more Smart Citation
“…This fact might have been anticipated by recalling that the net area under the imaginary part of the generalized phase integral, Z ( [ , x ) . is always positive (SMITHE et al, 1988).…”
Section: Cmentioning
confidence: 98%
“…The time dependence of R' is especially troublesome, since the imaginary part of the phase integral in z is no longer of definite sign (FAULCONER, 1987). In SMITHE et al (1988) it is shown that this more difficult phase integral may be performed semi-analytically by doing the parallel velocity summation prior to the time integration. It is also possible to perform the perpendicular velocity summation analytically.…”
Section: S U M Mmentioning
confidence: 99%
“…According to the analysis of Smithe et al [42], this approximation could lead to overestimating somewhat the efficiency of mode conversion in the vicinity of the magnetic axis. The code is, however, modular enough so that a more accurate evaluation of the integrals could be easily incorporated if a sufficiently fast algorithm for Z" in the form (55) becomes available.…”
Section: ~ ( ~ (W -mentioning
confidence: 99%
“…In this paper we neglect the effects (PERKINS, 1977) of magnetic field variation along the field lines (poloidal magnetic field effects) on the fast wave penetration and absorption in a Tokamak plasma. These effects can influence the ion cyclotron absorption ofafastwaveatlow k,, (KOVRIZHNYKH and MOROZ, 1985 ;GAMBIER and SAMAIN, 1985 ;SMITHE et al, 1988 ;BRAMBILLA, 1989)…”
Section: Plane Wave In An Homogeneous Plasmamentioning
confidence: 99%